Fungal infection : diagnosis and management - Richardson, M. D. (Wiley Online Library., 2012)
Fungal Infection: Diagnosis and Management, 4th Edition is a concise and up-to-date guide to the clinical manifestations, laboratory diagnosis and management of superficial, subcutaneous and systemic fungal infections. This highly acclaimed book has been extensively revised and updated throughout to ensure all drug and dosage recommendations are accurate and in agreement with current guidelines. A new chapter on infections caused by Pneumocystis jirovecii has been added. The book has been designed to enable rapid information retrieval and to help clinicians make informed decisions about diagnosis and patient management. Each chapter concludes with a list of recent key publications which have been carefully selected to facilitate efficient access to further information on specific aspects of fungal infections. Clinical microbiologists, infectious disease specialists, as well as dermatologists, hematologists and oncologists, can depend on this contemporary text for authoritative information and the background necessary to understand fungal infections --